LME for systems change via networked coalitions: A Synthesis note drawing on experience from the CGIAR climate resilience initiative’s policy transformation work stream. - Tabory, Samuel; Bell, Shavon; Gutierrez, Alberto Rivera; Ratner, Blake (2025)
This synthesis note addressing LME for networked systems change efforts builds on the experience of accompanying two networked coalition efforts for systems change in the agri-food sector as part of the CGIAR Climate Resilience Initiative (ClimBeR), within its work stream on policy transformation. The distillation of lessons is designed to feed into ongoing conversations about the development of operative LME framework guidance for such efforts, both within CGIAR programming and more broadly.